PENGARUH GAYA KEPEMIMPINAN DAN IKLIM SEKOLAH TERHADAP KINERJA GURU PADA SMK NEGERI DI KOTA SOLOK - Hendrizon Hendrizon (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2018)
Based on the observation that had done, it was known that the power teacher of SMK Negeri Kota Solok was stiil low. The aim of this research were to reveal the contribution of leadership of formal school climate toward the teachers performance. This research proposed three hypotheses: 1). There was contribution of leadership of formal toward the teachers performance, 2). There was contribution of school climate and toward the teachers performance and 3). There was contribution of leadership of formal and school climate toward the teachers performance. The population were 120 teachers of SMK Negeri 1 and 40 of SMK Negeri 3 Kota Solok. The sample were 60 teachers. This research used simple random sampling technique. The data were gathered by using Likert scale questionnaires whose validity and realiability had been tested. There result of the research revealed that 1). There was contribution of personal leadership of formal toward teachers performance (21,71 %):2): There was contribution of school climate toward teachers performance (12,32 %): and 3) There was contribution of personal leadership of formal and school climate toward teachers performance (10,32 %). These facts show that increase the teachers performance one should increase leadership of formal and school climate without neglecting other factors.